How soon will digital endpoints become a cornerstone for future drug development?. Issue 1 (January 2019) - Boehme, Philip; Hansen, Arne; Roubenoff, Ronenn; Scheeren, Joseph; Herrmann, Maximilian; Mondritzki, Thomas; Ehlers, Jan; Truebel, Hubert
Highlights: Late stage failures are decreasing productivity in Pharma R&D. Endpoints, non-reflective of patient needs, are not met causing late stage failure. The FDA encourages the use of digital technology to asses patients' needs. A consortium aims to get regulatory acceptance for real world walking speed. This collaborative approach will ensure patient centric innovation & endpoints. Abstract : Digital technologies are transforming healthcare and will provide the basis for more patient-centric innovation in the pharmaceutical industry. Digital endpoints in clinical studies have the potential to drive innovation and reduce costly late-stage failures. This is also currently under consideration by regulatory agencies, such as the US Food and Drug Administration (FDA). The academic–industrial collaboration MOBILISED-D aims to implement and validate real-world walking speed (RWS) as a digital endpoint accepted by regulatory authorities as a first of its class. Previous work has shown that loss of mobility driven by chronic illness and frailty in older patients can be a relevant readout or effect of different diseases and various organ systems.